Negative pole piece and preparation method thereof, and fast-charging lithium ion battery

By using graphite layered coating technology with different particle sizes on the negative electrode sheet of lithium-ion batteries, the OI value of each layer of graphite is limited and the ion impedance is reduced, and the problems of insufficient wettability and insufficient kinetic performance of the electrolyte are solved, and the High energy density and excellent rate performance.

CN119314992APending Publication Date: 2025-01-14RISESUN MENGGULI NEW ENERGY SCIENCE & TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310866937.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When the existing lithium-ion batteries increase the surface density, the increase in the thickness of the electrode sheet leads to insufficient wettability of the electrolyte and the increase in the lithium ion transmission path, resulting in poor rate performance and long-term cycle performance, making it difficult to take into account high energy density and good rate performance.

Method used

By using graphite layered coating technology with different particle sizes, the OI value of each layer of graphite material is defined, the ionic impedance of the electrode sheet is reduced and the rate performance of the electrode sheet is improved. The specific method includes coating the bottom layer and the upper coating on the negative electrode sheet. The particle size of the active material of the bottom coating material is smaller than that of the upper coating, and the OI value is ≤15. Combined with multiple rolling treatments, a negative electrode with a total thickness of 100-200μm is formed. piece.

Benefits of technology

The absorption rate of the electrolyte and the migration rate of lithium ions are improved, and the problems of poor wetting properties and insufficient kinetic performance of the electrolyte are solved, and high-quality energy density and high capacity retention are achieved, and the rate performance and cycle performance are excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314992A_ABST
    Figure CN119314992A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and discloses a negative pole piece, a preparation method of the negative pole piece and a quick-charge type lithium ion battery. The negative electrode plate comprises a negative electrode current collector, a bottom coating layer coated on the surface of the negative electrode current collector and an upper coating layer coated on the surface of the bottom coating layer, the active substance in the material of the bottom coating and the active substance in the material of the upper coating are respectively and independently graphite negative electrode materials, and the OI value of the active substance in the material of the bottom coating and the OI value of the active substance in the material of the upper coating are respectively and independently smaller than or equal to 15. Graphite with different OI values is adopted for layered coating, the ion impedance of the pole piece is reduced, the rate capability of the pole piece is improved, and the problem that the energy density and the rate capability cannot be considered at the same time due to insufficient electrolyte wettability, insufficient dynamic performance and poor conductivity caused by thickening of the negative pole piece is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and more specifically, relates to a negative electrode plate and a preparation method thereof and a fast-charging lithium-ion battery. Background Art

[0002] With the vigorous development of new energy vehicles, people have put forward higher requirements for the energy density and fast charging performance of lithium-ion secondary batteries, which are the "heart" of new energy vehicles. Among them, increasing the surface density of lithium-ion secondary batteries is an effective means to improve the energy density of lithium-ion batteries. However, when the surface density increases, the thickness of the pole piece increases accordingly, and problems such as difficulty in electrolyte infiltration, excessive lithium ion concentration gradient, increase in lithium ion transmission path, and uneven conductivity inside the pole piece appear, which leads to the deterioration of the battery's rate performance and long-term cycle performance, causing large-area lithium precipitation in the negative electrode. Researchers began to use layered coating technology, hoping to increase the fast charging performance of thick electrodes, but simply introducing layered coating technology cannot effectively alleviate the increase in lithium ion diffusion path caused by insufficient electrolyte wettability, thereby causing problems such as insufficient electrochemical kinetics and poor conductivity of composite electrodes, resulting in the battery being unable to take into account both high energy density and good rate performance.

[0003] Therefore, there is an urgent need to propose a new negative electrode plate and a preparation method thereof, and a fast-charging lithium-ion battery comprising the negative electrode plate. Summary of the invention

[0004] The purpose of the present invention is to provide a negative electrode sheet and a preparation method thereof and a fast-charge lithium-ion battery in view of the deficiencies of the prior art. The present invention adopts layered coating of graphite with different particle sizes, and at the same time limits the OI value of each layer of graphite material, thereby reducing the ionic impedance of the electrode sheet, improving the rate performance of the electrode sheet, and solving the problem that the energy density and rate performance cannot be taken into account due to insufficient electrolyte wettability, insufficient dynamic performance, and poor conductivity caused by the thickening of the negative electrode sheet.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode plate, which includes a negative electrode current collector, a bottom coating coated on the surface of the negative electrode current collector, and an upper coating coated on the surface of the bottom coating;

[0006] The active substance in the material of the bottom coating layer and the active substance in the material of the top coating layer are each independently a graphite-based negative electrode material, the particle size of the active substance in the material of the bottom coating layer is smaller than the particle size of the active substance in the material of the top coating layer, and the OI value of the active substance in the material of the bottom coating layer and the active substance in the material of the top coating layer is each independently ≤15.

[0007] According to the present invention, preferably, the OI values ​​of the active substances in the material of the bottom coating layer and the active substances in the material of the top coating layer are independently 10-15.

[0008] In the present invention, the OI value refers to the ratio of the intensity I(004) of the 004 crystal plane of the active material in the negative electrode plate to the intensity I(110) of the 110 crystal plane, so as to characterize the isotropy of the active material in the negative electrode plate.

[0009] According to the present invention, preferably, the total surface density of the negative electrode sheet is ≥10 mg / cm 2 .

[0010] According to the present invention, preferably, the total thickness of the negative electrode sheet is ≥100 μm, and the thickness of the bottom coating is ≤ the thickness of the upper coating; preferably, the total thickness of the negative electrode sheet is 100-200 μm, and more preferably, the bottom coating and the upper coating are of equal thickness;

[0011] In the present invention, the symmetrical battery prepared by the negative electrode plate of the present invention is tested for its electrochemical impedance at 100kHz to 100mHz, and the ionic impedance of the plate is obtained by fitting the analog circuit L1 (inductance) + R (resistance) + Ma (diffusion impedance), so as to characterize the resistance encountered by lithium ions in the migration of the internal electrode plate. According to the present invention, preferably, the ionic resistance of the negative electrode plate is 8-22ohm*cm 2 , preferably 8-18ohm*cm 2 .

[0012] According to the present invention, preferably, the active substance in the material of the base coating layer includes artificial graphite and / or natural graphite.

[0013] According to the present invention, preferably, the active substance in the material of the upper coating layer includes at least one of artificial graphite, natural graphite and mesophase carbon microbeads.

[0014] According to the present invention, preferably, the negative electrode current collector is at least one of carbon-coated copper foil, copper foil and carbon fiber.

[0015] According to the present invention, preferably, the material of the base coating layer also includes a base conductive agent, a base binder and a base thickener; preferably, the material of the base coating layer includes the following components in parts by weight: 95-98 parts of active substances in the material of the base coating layer, 0.5-2 parts of base conductive agents, 1-2 parts of base binders and 1-2 parts of base thickeners.

[0016] According to the present invention, preferably, the material of the upper coating layer also includes an upper conductive agent, an upper binder and an upper thickener; preferably, the material of the upper coating layer includes the following components in parts by weight: 95-98 parts of active substances in the material of the upper coating layer, 0.5-2 parts of upper conductive agent, 1-2 parts of upper binder and 1-2 parts of upper thickener.

[0017] According to the present invention, preferably, the bottom conductive agent and the upper conductive agent are each independently at least one of conductive carbon black, conductive graphite, carbon nanotubes and graphene; preferably, the graphene has a particle size of 4-8 μm and a layer number of ≤10 layers.

[0018] According to the present invention, preferably, the bottom layer thickener and the upper layer thickener are each independently selected from at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride, lithium polyacrylate and polyacrylonitrile.

[0019] According to the present invention, preferably, the bottom layer adhesive is a water-based adhesive with a glass transition temperature of ≤100°C; preferably, the bottom layer adhesive is at least one of polystyrene-1,3-butadiene, butadiene and polyacrylate.

[0020] According to the present invention, preferably, the upper layer binder is a water-based binder with a glass transition temperature ≥ 120°C; preferably, the upper layer binder comprises at least one of polyacrylonitrile copolymer, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate and polyethylene oxide.

[0021] The second aspect of the present invention provides a method for preparing the negative electrode sheet, the method comprising the following steps:

[0022] S1: mixing the material of the bottom coating with water and stirring evenly to obtain a bottom coating slurry; mixing the material of the top coating with water and stirring evenly to obtain a top coating slurry;

[0023] S2: applying the bottom coating slurry to the surface of the current collector to form a bottom coating; applying the top coating slurry to the surface of the bottom coating;

[0024] S3: drying and rolling the current collector coated in step S2 in sequence to obtain the negative electrode sheet.

[0025] According to the present invention, preferably, the usage ratio of the material of the base coating to water is 100:(75-85).

[0026] According to the present invention, preferably, the usage ratio of the material of the upper coating layer to water is 100:(75-85).

[0027] According to the present invention, preferably, the roller pressing process is performed 2-3 times.

[0028] The third aspect of the present invention provides a fast-charging lithium-ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte;

[0029] The negative electrode plate is the negative electrode plate mentioned above.

[0030] According to the present invention, preferably, the ionic resistance of the positive electrode plate is 5-15 ohm*cm 2 , single-sided surface density is controlled at 12-18mg / cm 2 .

[0031] According to the present invention, preferably, the positive electrode plate comprises a positive electrode current collector and an active material layer coated on the surface of the positive electrode current collector; the material of the active material layer is a high-nickel ternary material, preferably LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0032] According to the present invention, preferably, the energy density of the battery reaches 274-280wh / kg, the fast charging time is ≤15min, and the cycle life exceeds 2000 times.

[0033] In the present invention, the fast-charging lithium-ion battery is preferably at least one of a soft-pack, steel-shell packaged laminated, and wound battery.

[0034] The beneficial effects of the technical solution of the present invention are as follows:

[0035] The present invention adopts layered coating of graphite with different particle sizes and adopts multiple rolling processes to prepare negative electrode plates, and at the same time limits the OI value of the graphite of each layer, thereby reducing the ionic impedance of the plate and improving the rate performance of the plate, that is, improving the absorption rate of the electrolyte and the migration rate of lithium ions, and allowing electrons at the current collector to quickly enter or escape, thereby solving the problem of poor electrolyte wettability and insufficient kinetic performance caused by the excessive thickness of the negative electrode plate, while taking into account the good conductivity of the negative electrode plate, so that the lithium ion battery using the negative electrode plate of the present invention has high mass energy density and high capacity retention rate, and excellent rate performance and cycle performance.

[0036] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0038] Figure 1A schematic diagram showing the fast charge cycle performance of the fast charge lithium ion battery of Example 1 of the present invention and Comparative Examples 1-2. (Row Numbers represent the number of cycles) DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0040] Example 1

[0041] This embodiment provides a negative electrode plate, which includes a negative electrode current collector, a bottom coating layer coated on the surface of the negative electrode current collector, and an upper coating layer coated on the surface of the bottom coating layer;

[0042] The relationship between the OI value, particle size and thickness of the active material in the material of the bottom coating layer and the active material in the material of the top coating layer is shown in Table 1.

[0043] The active material in the material of the bottom coating is artificial graphite (specific capacity is 350 mAh / g), and the material of the bottom coating also includes bottom conductive agent conductive carbon black, bottom binder polystyrene-1,3 butadiene and bottom thickener sodium carboxymethyl cellulose; the weight ratio of artificial graphite: conductive carbon black: sodium carboxymethyl cellulose: polystyrene-1,3 butadiene is 97.1:0.5:1.2:1.2;

[0044] The active material in the material of the upper coating layer is artificial graphite (specific capacity is 340 mAh / g), and the material of the upper coating layer also includes an upper conductive agent conductive carbon black, an upper binder polystyrene-1,3 butadiene and an upper thickener sodium carboxymethyl cellulose; the weight ratio of artificial graphite: conductive carbon black: sodium carboxymethyl cellulose: polystyrene-1,3 butadiene is 97.1:0.5:1.2:1.2;

[0045] The negative electrode current collector is copper foil.

[0046] The method for preparing the negative electrode sheet comprises the following steps:

[0047] S1: Mix the above-mentioned bottom coating material with water and stir evenly to obtain a bottom coating slurry; mix the above-mentioned top coating material with water and stir evenly to obtain a top coating slurry; the amount ratio of the bottom coating material to water is 100:80; the amount ratio of the top coating material to water is 100:80;

[0048] S2: The negative electrode sheet is coated with a single-sided weight of 12 mg / cm 2 , a base coating and an upper coating are applied on both sides of a copper foil with a thickness of 8 μm, the base coating is applied on the surface of the copper foil, and the upper coating is applied on the base coating, followed by drying and rolling, to form a thick electrode with a total thickness of 179 μm (the compaction density of the electrode is 1.5 g / cm 3 ), wherein the thickness of the bottom coating and the upper coating are both 43 μm, and the thickness ratio is 1:1, and then the negative electrode sheet is obtained through a cutting process.

[0049] This embodiment also provides a fast-charging lithium-ion battery, which is a stacked 20Ah soft-pack battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the performance parameters are shown in Table 2.

[0050] The negative electrode plate is the negative electrode plate mentioned above.

[0051] The positive electrode plate is LiNi 0.8 Co 0.1 Mn 0.1 O2 was mixed with binder polyvinylidene fluoride, conductive carbon black, and carbon nanotube slurry in a weight ratio of 97.2:1:0.6:1.2. 40 parts by weight of N-methyl-2-pyrrolidone was added to 100 parts by weight of the mixture and mixed by a planetary mixer to obtain a positive electrode slurry. Then, a conventional single-cavity extrusion coating die was used to coat the cathode slurry at a single-side coating weight of 17.5 mg / cm 2 , evenly coated on both sides of 13μm aluminum foil, and then dried, rolled, die-cut, slit and cut to obtain the positive electrode sheet.

[0052] The electrolyte is prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1, adding lithium salt LiPF6 after sufficient stirring, and mixing evenly to obtain an electrolyte, wherein the concentration of LiPF6 is 1.10 mol / L.

[0053] The diaphragm is a ceramic diaphragm

[0054] The preparation of the battery includes:

[0055] The positive electrode sheet, negative electrode sheet and ceramic separator prepared above are stacked into a soft-pack battery cell, which is baked under vacuum for 24 hours to remove moisture, and then injected with electrolyte. The battery is subjected to formation, capacity division, OCV and sorting to obtain the fast-charging lithium-ion battery, which is recorded as A1.

[0056] Comparative Example 1

[0057] This comparative example provides a negative electrode sheet, and the difference between this comparative example and Example 1 is only that:

[0058] The relationship between the OI value, particle size and thickness of the active material in the coating material of the negative electrode plate is shown in Table 1. The active material in the coating material is artificial graphite (specific capacity is 350 mAh / g), and the material of the bottom coating also includes bottom conductive agent conductive carbon black, bottom binder polystyrene-1,3 butadiene and bottom thickener sodium carboxymethyl cellulose; the weight ratio of artificial graphite: conductive carbon black: sodium carboxymethyl cellulose: polystyrene-1,3 butadiene is 97.1:0.5:1.2:1.2;

[0059] The method for preparing the negative electrode sheet comprises the following steps:

[0060] S1: Mix the coating material and water and stir them evenly to obtain a coating slurry; the ratio of the coating material to water is 100:80;

[0061] S2: The negative electrode sheet is coated with a single-sided weight of 12 mg / cm 2 , coated on both sides of the 8μm thick copper foil, followed by drying and secondary rolling, to form a thick electrode with a total thickness of about 176μm (the compaction density of the electrode is 1.5g / cm 3 ), and then the negative electrode sheet is obtained through a cutting process.

[0062] This comparative example also provides a fast-charging lithium-ion battery, which is a stacked 20Ah soft-pack battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the performance parameters are shown in Table 2.

[0063] The negative electrode plate is the negative electrode plate mentioned above.

[0064] The positive electrode plate, electrolyte, separator, and battery preparation method are the same as those in Example 1 to obtain the fast-charging lithium-ion battery, which is denoted as C1.

[0065] Comparative Example 2

[0066] This comparative example provides a negative electrode sheet, and the difference between this comparative example and Example 1 is only that:

[0067] The relationship between the OI value, particle size and thickness of the active material in the material of the bottom coating layer and the active material in the material of the top coating layer is shown in Table 1.

[0068] Other materials and preparation methods are the same as those in Example 1.

[0069] This comparative example also provides a fast-charging lithium-ion battery, which is a stacked 20Ah soft-pack battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the performance parameters are shown in Table 2.

[0070] The negative electrode plate is the negative electrode plate mentioned above.

[0071] The positive electrode plate, electrolyte, separator, and battery preparation method are the same as those in Example 1 to obtain the fast-charging lithium-ion battery, which is denoted as C2.

[0072] Table 1

[0073]

[0074] Table 2

[0075]

[0076]

[0077] Table 3

[0078]

[0079] It can be seen from Tables 1, 2 and 3 that the OI value of the negative electrode coating of Example A1 is ≤15, and the ionic impedance of the electrode piece is 10-18 ohm*cm 2 , the battery rate charging capacity is relatively high. Under the condition of the same energy density, layered coating can reduce the ionic impedance of the pole piece, the DC internal resistance and temperature rise of the battery, and improve the fast charging cycle performance of the battery. Figure 1 It can be seen that the 15-min fast charge cycle performance of the negative electrode is significantly improved by using a layered coating system with an OI value of ≤15. Although Comparative Example C2 uses graphites of different particle sizes for layered coating, the OI value of the bottom layer is large (over 15), and the fast charge cycle performance is worse than that of Example A1.

[0080] In summary, in the manufacturing process of the fast-charging lithium-ion battery of the present invention, the negative electrode plate is coated in layers to control the OI value of the plate, reduce the ionic impedance of the plate, increase the absorption rate of the electrolyte and the migration rate of lithium ions, and improve the wettability and kinetic performance of the negative electrode plate electrolyte, so that the battery has high quality energy density and high capacity retention rate, and excellent rate performance and cycle performance.

[0081] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector, a bottom coating layer coated on the surface of the negative electrode current collector, and an upper coating layer coated on the surface of the bottom coating layer; The active substance in the material of the bottom coating layer and the active substance in the material of the top coating layer are each independently a graphite-based negative electrode material, the particle size of the active substance in the material of the bottom coating layer is smaller than the particle size of the active substance in the material of the top coating layer, and the OI value of the active substance in the material of the bottom coating layer and the active substance in the material of the top coating layer is each independently ≤15.

2. The negative electrode sheet according to claim 1, wherein: The OI values ​​of the active substances in the material of the bottom coating layer and the active substances in the material of the top coating layer are independently 10-15.

3. The negative electrode sheet according to claim 1 or 2, wherein: The total surface density of the negative electrode sheet is ≥10 mg / cm 2 ; The total thickness of the negative electrode sheet is ≥100 μm, and the thickness of the bottom coating is ≤ the thickness of the top coating; preferably, the total thickness of the negative electrode sheet is 100-200 μm, and more preferably, the bottom coating and the top coating are of equal thickness; The ionic resistance of the negative electrode plate is 8-22 ohm*cm 2 , preferably 8-18ohm*cm 2 .

4. The negative electrode sheet according to claim 1 or 2, wherein: The active substance in the material of the base coating layer includes artificial graphite and / or natural graphite; The active material in the material of the upper coating layer includes at least one of artificial graphite, natural graphite and mesophase carbon microspheres; The negative electrode current collector is at least one of carbon-coated copper foil, copper foil and carbon fiber.

5. The negative electrode sheet according to claim 1 or 2, wherein: The material of the bottom coating layer further comprises a bottom conductive agent, a bottom binder and a bottom thickener; preferably, the material of the bottom coating layer comprises the following components in parts by weight: 95-98 parts of active material in the material of the bottom coating layer, 0.5-2 parts of bottom conductive agent, 1-2 parts of bottom binder and 1-2 parts of bottom thickener; The material of the upper coating layer also includes an upper conductive agent, an upper binder and an upper thickener; preferably, the material of the upper coating layer includes the following components in parts by weight: 95-98 parts of active substances in the material of the upper coating layer, 0.5-2 parts of upper conductive agent, 1-2 parts of upper binder and 1-2 parts of upper thickener.

6. The negative electrode sheet according to claim 5, wherein: The bottom conductive agent and the upper conductive agent are each independently at least one of conductive carbon black, conductive graphite, carbon nanotubes and graphene; preferably, the graphene has a particle size of 4-8 μm and a layer number of ≤10; The bottom layer thickener and the upper layer thickener are each independently selected from at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride, lithium polyacrylate and polyacrylonitrile; The bottom layer binder is a water-based binder with a glass transition temperature of ≤100°C; preferably, the bottom layer binder is at least one of polystyrene-1,3-butadiene, butadiene and polyacrylate; The upper layer binder is a water-based binder with a glass transition temperature of ≥120° C.; preferably, the upper layer binder comprises at least one of polyacrylonitrile copolymer, polyethylene carbonate, polypropylene carbonate, polyvinylene carbonate and polyethylene oxide.

7. The method for preparing a negative electrode sheet according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: S1: mixing the material of the bottom coating with water and stirring evenly to obtain a bottom coating slurry; mixing the material of the top coating with water and stirring evenly to obtain a top coating slurry; S2: applying the bottom coating slurry to the surface of the current collector to form a bottom coating; applying the top coating slurry to the surface of the bottom coating; S3: drying and rolling the current collector coated in step S2 in sequence to obtain the negative electrode sheet.

8. The method for preparing a negative electrode sheet according to claim 7, wherein: The ratio of the material of the bottom coating to water is 100:(75-85); The ratio of the material of the upper coating to water is 100:(75-85); The number of times of the roller pressing treatment is 2-3 times.

9. A fast-charge lithium-ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; The negative electrode plate is the negative electrode plate according to any one of claims 1 to 6.

10. The fast-chargeable lithium-ion battery according to claim 9, wherein: The ionic resistance of the positive electrode plate is 5-15 ohm*cm 2 , single-sided surface density is controlled at 12-18mg / cm 2 ; The positive electrode plate comprises a positive electrode current collector and an active material layer coated on the surface of the positive electrode current collector; the material of the active material layer is a high-nickel ternary material, preferably LiNi 0.8 Co 0.1 Mn 0.1 O2. The energy density of the battery reaches 274-280wh / kg, the fast charging time is ≤15min, and the cycle life exceeds 2000 times.

Citation Information

Cited By

  • Negative plate, preparation method thereof and battery

    CN120637386A

  • Negative electrode sheet, method for manufacturing the same, and battery

    CN120637386B